Comparison of Adverse Maternal Outcomes between Early- and Late-Onset Superimposed Preeclampsia - Onishi, Kazuma; Seagraves, Elizabeth; Baraki, Dana; Donaldson, Thomas; Barake, Carole; Abuhamad, Alfred; Huang, Jim C.; Kawakita, Tetsuya (American Journal of Perinatology, 2023)
Objective Superimposed preeclampsia (SIPE), defined as preeclampsia in individuals with chronic hypertension, is one of the most common complications, accounting for 13 to 40% of pregnancies with chronic hypertension. However, there are limited data regarding maternal outcomes of early- and late-onset SIPE in individuals with chronic hypertension. We hypothesized that early-onset SIPE was associated with increased odds of adverse maternal outcomes compared with late-onset SIPE. Therefore, we aimed to compare adverse maternal outcomes between individuals with early-onset SIPE and those with late-onset SIPE.Study Design This was a retrospective cohort study of pregnant individuals with SIPE who delivered at 22 weeks' gestation or greater at an academic institution. Early-onset SIPE was defined as the onset of SIPE before 34 weeks' gestation. Late-onset SIPE was defined as the onset of SIPE at or after 34 weeks' gestation. Our primary outcome was a composite of eclampsia, hemolysis, elevated liver enzymes, low platelet count (HELLP) syndrome, maternal death, placental abruption, pulmonary edema, SIPE with severe features, and thromboembolic disease. Maternal outcomes were compared between early- and late-onset SIPE. We used simple and multivariate logistic regression models to calculate crude and adjusted odds ratios (aOR) with 95% confidence intervals (95% CI).Results Of 311 individuals, 157 (50.5%) had early-onset SIPE, 154 (49.5%) had late-onset SIPE. There were significant differences in the proportions of obstetric complications, including the primary outcome, HELLP syndrome, SIPE with severe features, fetal growth restriction (FGR), and cesarean delivery between early- and late-onset SIPE. Compared with individuals with late-onset SIPE, those with early-onset SIPE had increased odds of the primary outcome (aOR: 3.28; 95% CI: 1.42–7.59), SIPE with severe features (aOR: 2.72; 95% CI: 1.25–5.90), FGR (aOR: 6.07; 95% CI: 3.25–11.36), and cesarean delivery (aOR 3.42; 95% CI: 2.03–5.75).Conclusion Individuals with early-onset SIPE had higher odds of adverse maternal outcomes compared with those with late-onset SIPE.Key Points
Keywords: chronic hypertension; eclampsia; fetus growth restriction; HELLP; placental abruption; pulmonary edema; preeclampsia with severe features; thromboembolism